At-home use of parasacral transcutaneous electrical nerve stimulation for pediatric voiding dysfunction: a randomized controlled trial to assess its safety and feasibility - Malhotra, Neha R.; Siegal, Alexandra R.; Lange, Suzanne M.; Cervantez, DeeAnn; White, Heidi K.; Hannon, AnnMarie; Schaeffer, Anthony J.; Lau, Glen A. (Frontiers in Pediatrics, 2023)
Introduction: Treatment of pediatric voiding dysfunction involves behavioral changes that require significant time investment or medications that are often avoided or discontinued due to side effects. Use of parasacral transcutaneous electrical nerve stimulation (PTENS) has shown to have reasonable efficacy, but the safety and feasibility of its off-label use for pediatric voiding dysfunction is not well-established. Concerns have also been raised over treatment adherence. Adherence might be improved by in-home as opposed to office-based therapy; however, to date, no studies have evaluated in-home feasibility. The aim of this study is to assess the safety and feasibility of off-label use of PTENS for pediatric voiding dysfunction. Materials and methods: A single-institution prospective, randomized controlled study was conducted from March 2019 to March 2020. Participants aged 6 to 18 years with a diagnosis of voiding dysfunction, overactive bladder, or urinary incontinence were eligible. Those with known neurologic disorders, implanted electrical devices, anatomic lower urinary tract abnormality, recurrent urinary tract infections, and use of bladder medications were excluded. Children with primary monosymptomatic nocturnal enuresis were also excluded given prior work suggesting a lack of efficacy. Participants were randomized to either 12 weeks of urotherapy (control) or urotherapy plus home PTENS treatment. Families were contacted weekly to assess for adverse events (AE) and treatment adherence. The primary and secondary outcomes were safety, defined as the absence of AE, and treatment adherence. Results: Thirty eligible participants were randomized with 15 in each arm. Median age was 9.4 years [IQR 7.7 – 10.6]. 60% were male. Baseline demographics and urotherapy compliance were similar amongst groups. With PTENS use, there were two AE including mild pruritus at the pad site and discomfort when removing pads versus none in the control. 60% of patients completed three 30-minute sessions per week; all participants were able to complete treatments sessions for at least ten weeks and were able to complete 30 minutes of PTENS treatment when used. Conclusion: This randomized controlled study confirms that at-home use of PTENS is feasible with reasonable treatment adherence and minimal AE. Future collaborative, multi-institutional studies may better determine the efficacy of this treatment modality.